Environmental racism and health: a study of the Santa Maria neighborhood in Aracaju (SE) - Soares Santos, Josiane (2023)
The text exposes data from a research on the Santa Maria neighborhood, located in Aracaju/Sergipe, aiming to characterize expressions of “environmental racism” in the configuration of health as part of the so-called “right to the city”. The result shows that environmental racism was expressed in the decision of the government regarding the place of operation of the open-air garbage dump in the city of Aracaju. Moreover, it is also expressed in the negligence of the government regarding the environmental sanitation measures necessary for that area of housing that lived for 27 years with this garbage dump. In the final considerations, we show consequences of this environmental racism using data from the Covid-19 pandemic, indicating that the indistinct planning of actions to combat it by the municipality of Aracaju seems to have, intentionally or not, disregarded the socio-environmental and racial inequalities historically present in the different areas of housing in the city.